2020
DOI: 10.1097/01.aog.0000663472.60779.74
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Obesity on Maternal and Neonatal Outcomes in Advanced Maternal Age Women [22D]

Abstract: INTRODUCTION: Advanced maternal age (AMA) and obesity have been shown to independently influence maternal and neonatal outcomes. We sought to determine if obese AMA women had greater risk for adverse outcomes compared to non-obese AMA women. METHODS: A retrospective cohort study of non-anomalous, singleton AMA (age 35+) pregnancies at Oregon Health & Science University from 2009–2014 to assess if obesity (pre-pregnancy BMI 30+) impacted outcomes abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…17 The stigma surrounding the diagnosis of obesity can be seen in past recommendations in which pregnancy care was heavily focused on intervention for patients with a BMI over 30 kg/m 2 . 12,18 The current recommendations focus on collaboration between low-and high-risk providers, and the result of this trend toward collaborative practices has improved patient outcomes. 9,19 In support of this, a growing body of research shows improved outcomes when the pregnant person has access to the Midwifery Model of Care-a model very familiar to women's health nurse practitioners.…”
Section: Difficulty Breastfeedingmentioning
confidence: 99%
“…17 The stigma surrounding the diagnosis of obesity can be seen in past recommendations in which pregnancy care was heavily focused on intervention for patients with a BMI over 30 kg/m 2 . 12,18 The current recommendations focus on collaboration between low-and high-risk providers, and the result of this trend toward collaborative practices has improved patient outcomes. 9,19 In support of this, a growing body of research shows improved outcomes when the pregnant person has access to the Midwifery Model of Care-a model very familiar to women's health nurse practitioners.…”
Section: Difficulty Breastfeedingmentioning
confidence: 99%
“…Liu et al, (2013) found that of neonatal intensive care admission (AOR, 2.07; 95% CI, 1.32-3.23) and Apgar score of under 7 at 5 minutes (95%) in overweight compared with normal weight [20] . Also Hartge et al, (2016) , and Hanneman et al,( 2020) found that neonates born to obese women were associated with significantly increased rates of hypoglycemia (95%) [21,22] . 2014) who found no significant association between women weight and neonatal outcomes, risks of stillbirth, neonatal death, preterm birth, congenital anomaly, and low birth weight [22,23,24] .…”
Section: Simple Linear Regression For Assessment the Impact Of Normal And Overweight Upon Neonate Outcomes Among Pregnant Women (Table 4)mentioning
confidence: 99%
“…Also Hartge et al, (2016) , and Hanneman et al,( 2020) found that neonates born to obese women were associated with significantly increased rates of hypoglycemia (95%) [21,22] . 2014) who found no significant association between women weight and neonatal outcomes, risks of stillbirth, neonatal death, preterm birth, congenital anomaly, and low birth weight [22,23,24] .…”
Section: Simple Linear Regression For Assessment the Impact Of Normal And Overweight Upon Neonate Outcomes Among Pregnant Women (Table 4)mentioning
confidence: 99%